Paternal experience during the child's first year of life: integrative review of qualitative research - Fernando Henrique Ferreira; Monika Wernet; Bruna de Souza Lima Marski; Graziani Izidoro Ferreira; Laura Priscila Navarrete de Toledo; Márcia Regina Cangiani Fabbro (Universidade Federal de Goias, 2015)
Social transformations have raised reflection about the paternal role and pointed to new fatherhoods, characterized by more effective involvement of the father in the family routine and in childcare. The present integrative review of qualitative studies aimed to synthetize the literature evidence about fatherhood experience throughout the first year of the child's life, attentive to gender questions. Twenty three studies integrated this review. It was observed that fathers had positive experience with their babies and, still, craved for more time and space to dedicate to the family. However, inequality between genders, continuous requirement of financial provision at home and their inaptitude for breastfeeding moment impeded more paternal involvement. We concluded that new fatherhoods movement is present in the father experience and contemporary gender tendencies are challenges for parenting support.